1981
DOI: 10.1007/bf03216218
|View full text |Cite
|
Sign up to set email alerts
|

Severely uncontrolled diabetes in the over-fifties

Abstract: Between 1969 and 1976, 317 adults were admitted to hospital in Nottingham with severely uncontrolled diabetes (plasma glucose over 33 mmol/l and/or venous bicarbonate less than 14 mmol/l). A third of episodes were in patients over the age of 50 years, of which 43% were fatal. In contrast, only 3.4% of episodes in patients under 50 years were fatal. In the older group, 65% of deaths occurred within 48 h of admission and in 44% no cause was found other than uncontrolled diabetes. Later deaths were due to underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
1
1

Year Published

1983
1983
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 17 publications
3
16
1
1
Order By: Relevance
“…However, the existing diabetes registry does not seem to be adequate for identifying incident cases in persons older than 50 years. Early fatality seems to influence the incidence rates in this age group, since 14 % of incident cases in this age group was identified solely through death certificates, thus supporting data on the high mortality of newly-diagnosed IDDM in the elderly [18]. Of the patients who died before being registered, none had had diabetes diagnosed previously.…”
Section: Discussionsupporting
confidence: 68%
“…However, the existing diabetes registry does not seem to be adequate for identifying incident cases in persons older than 50 years. Early fatality seems to influence the incidence rates in this age group, since 14 % of incident cases in this age group was identified solely through death certificates, thus supporting data on the high mortality of newly-diagnosed IDDM in the elderly [18]. Of the patients who died before being registered, none had had diabetes diagnosed previously.…”
Section: Discussionsupporting
confidence: 68%
“…The reasons for this are manifold. There is uncertainty about whether the patient will benefit from insulin treatment or will be able to leam the injection technique, as well as a fear of hypoglycaemia and weight gain (5, 8,10,11). When insulin treatment is really needed, many of these patients are referred to a hospital (12), although it has been shown that better metabolic control can also be obtained, in insulin dependent diabetic patients, if insulin treatment is started in an outpatient clinic (13.14).…”
mentioning
confidence: 99%
“…There are experimental findings to endorse the opposite view that insulin does not aggregate its own receptor [2,4,5]. Receptor aggregation, nevertheless, does occur in the natural state of certain tissues [2,9] and may not be necessary as a primary mechanism for insulin action.…”
mentioning
confidence: 94%
“…There have recently been several reports of haemostatic changes in diabetic coma [2, 31 and, while a coagulopathy may exist, its association with fatal thromboembolic events has not been established. In the hope of decreasing mortality from fatal thromboembolism and, in turn, lowering overall mortality from uncontrolled diabetes (up to 50% in the elderly [4]) some investigators have proposed prophylactic anticoagulation in these patients [5][6][7][8]. This has gained increased support in the literature and while antiplatelet drugs are not recommended, it has been suggested that heparin may be warranted in high risk uncontrolled diabetic patients.…”
Section: Antiplatelet/anticoagulant Drug Therapy In Severely Uncontromentioning
confidence: 99%
See 1 more Smart Citation